Research and Development to Improving Deformation Performance of Wire Rope Barriers - HIRASAWA, Masayuki; ITO, Yasuhiko; YAMADA, Keita (Journal of the Eastern Asia Society for Transportation Studies, 2024)
Buffer-type wire rope barriers are useful for installation on existing roads and narrow median strips as they have thin posts and require only a narrow width for installation. However, due to their structural property of absorbing the impact of collisions with vehicles by warping, it was difficult to improve their deformation performance in case of vehicle collisions. In this study, a rope interlocking member that reduces the amount of protrusion into the opposite lane in case of vehicle collisions was developed to improve the performance of wire rope barriers, and the optimal specifications were determined by conducting a large vehicle collision test. As a result, the amount of protrusion into the opposite lane in case of collisions with large vehicles was reduced by approximately 60% and the deformation performance was improved 2.5 times.